Assessment of genetic stability and photoreceptor gene expression (CmPHYA and CmPHYB ) of Chrysanthemum indicium plantlets culture on medium containing molybdenum trioxide nanoparticles - Duong, Tan Nhut; Phan, Le Ha Nguyen; Nguyen, Thi Nhu Mai; Do, Manh Cuong; Hoang, Hai Dang; Vu, Quoc Luan; Hoang, Thanh Tung; Hoang, Thi Nhu Phuong; Van, Hong Thien; Nguyen, Quang Vinh; et al. (Vietnam Journal of Biotechnology, 2025)
This study investigated the effects of molybdenum trioxide nanoparticles (MoO₃NPs) on the rooting, genetic stability, photosynthesis-related gene expression, and nursery-stage growth of Chrysanthemum indicum. The rooting stage analysis revealed that the 6.4 µg/L MoO₃NPs treatment significantly enhanced rooting rate, plantlet height, leaf number, root number, root length, SPAD value, and fresh weight compared to control treatments. ITS sequence analysis confirmed that MoO₃NPs did not induce mutations or genetic instability, with the ITS sequences of treated plantlets showing 100% similarity with those in the NCBI database and control samples. MoO₃NPs supplementation also upregulated the expression of CmPHYA and CmPHYB, critical genes encoding photoreceptors involved in red and far-red light perception, enhancing photosynthetic efficiency. At the nursery stage, plantlets derived from MoO₃NPs-supplemented media demonstrated superior growth parameters, including plant height, leaf and root numbers, fresh and dry weight, and SPAD value. These findings underscore the potential of MoO₃NPs to improve plantlet development, photosynthetic performance, and nutrient absorption, thereby highlighting their role in sustainable plant production systems.